Phase diagram determination and thermodynamic modeling of the Cu-Mg-Si system - Zhao, Jingrui; Zhou, Jixue; Liu, Shuhong; Du, Yong; Tang, Shouqiu; Yang, Yuansheng (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
13 ternary Cu-Mg-Si alloys were prepared by means of the powder metallurgy method. Phase equilibria at 500 and 700oC of the Cu-Mg-Si system were determined using X-ray diffraction analysis (XRD). The existence of 3 ternary compounds in this system was verified: Sigma (Cu16Mg6Si7), Tau (Cu3Mg2Si), and Laves ((Cu0.8Si0.2)2(Mg0.88Cu0.12)). A thermodynamic modeling for the Cu-Mg-Si system was then conducted on the basis of the experimental data obtained in this work and those critically reviewed from the literature. The complex phase relationship between Laves phase and other phases has been successfully modeled in this work. Comparisons between the calculated and the measured phase diagrams show that most of the experimental data can be reproduced by the presently obtained thermodynamic parameters.